BEYOND THE TEST: DEVELOPING AND VALIDATING A DIGITAL FORMATIVE ASSESSMENT TOOL FOR MEASURING COLLABORATIVE PROBLEM-SOLVING SKILLS - Ali, Ahmed; Ibrahim, Fadumo; Ahmed, Mohamed (Yayasan Adra Karima Hubbi, 2025)
In the context of modern education, collaborative problem-solving (CPS) has become a crucial skill for students to develop, as it directly impacts their ability to work in teams and solve real-world problems. However, existing assessment tools often fail to capture the full scope of CPS abilities, particularly in collaborative settings. This study aims to develop and validate a digital formative assessment tool designed to measure collaborative problem-solving skills in students. The tool incorporates both individual and group-based problem-solving tasks, aligning with the principles of authentic learning experiences. A mixed-methods approach was used, combining the development of the assessment tool with a validation process involving expert reviews, pilot testing, and statistical analysis of the tool’s reliability and validity. The results indicated that the tool demonstrated strong validity and reliability, with significant improvements in students' CPS skills being observed after engaging with the digital assessment. This study concludes that a well-designed digital formative assessment tool can effectively measure collaborative problem-solving abilities and provide valuable feedback for students and educators. The findings contribute to the growing body of research on digital assessment tools and offer practical implications for educators seeking to foster collaborative skills in the classroom.